Community engagement and civic participation in education: The role of education in advancing social capital among rural communities. - Ibrahim, Yasmine Ali Mohamed (AUC Knowledge Fountain, 2016)

(untitled)
This thesis examines e the role of civic participation in education in building the capacities of rural communities and advancing behaviors of democracy through the formation of a culture of social capital among them.